THE SIGNIFICANCE OF QUANTITIES DETECTION OF СORE ANTIGEN IN BLOOD SERUM OF CHILDREN WITH HEPATITIS C - A. Leybman; L. I. Nikolaeva; G. V. Sapronov; E. I. Shestakova; E. I. Samokhvalov; O. B. Kovalev; A. G. Pisarev; L. I. Konovalova; A. E. Grishechkin; V. F. Uchaikin (Детские инфекции (Москва))
The clinical and pathogenetic significance of determining HCV core-antigen (HCV core-Ag) in serum of children with hepatitis C was investigated firstly. A direct correlation between the concentration of HCV core-Ag and viral load (VL) was revealed (r = 0,91). Children with high core-Ag (above 2500 fmol/L) showed indirect evidence for the immunosuppressive action of HCV core-Ag and occurrence of liver fibrosis more frequent (p < 0,05). In this grouP of children the prevalence of HCV subtype 3a was revealed (p < 0,05).